The philosophy of neo-noir - Conard, Mark T., 1965- (Philosophy of popular culture., 2007)
Film noir--a cycle of American films from the 1940s and '50s--is characterized not only by a constant opposition of light and shadow and a disruptive compositional balance of frames and scenes, but also by dark, foreboding characters and plots and an overriding sense of alienation and moral ambiguity. Noir films reflect the sense of loss, fragmentation, and nihilism at the heart of the human condition in the twentieth century. Although the classic film noir period ended in the late 1950s, its impact on more films has been profound. While typically not black and white, these new films incorpor.